Penyidikan Terhadap Pelaku Tindak Pidana Penggelapan Mobil Rental oleh Kepolisian Resor Kota Pekanbaru - Selvy Yustunika; Dessy Artina; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Indonesia is a developing country, in a developing country the fulfillment of economic needs and motor vehicle facilities, especially cars, is very important for its people. With the higher needs, the higher the risk of crime. The crime of embezzlement of rental cars has happened a lot in people's lives. The embezzlement was carried out by the perpetrators to fulfill the necessities of life, with many car rental fraud embezzlement now it is necessary to consider quick action by the investigators regarding the background and mode of the fraud of the rental car embezzlement as well as how criminal liability against the embezzler of the rental car embezzlement that causes the occurrence of the acts embezzlement.The type of legal research used by the author is the type of sociological research, which is field research to see the effectiveness of law. According to Soejono Soekanto that in sociological legal research can see the correlation between law and society so that it can reveal the effectiveness of the law in society and identify unwritten laws that apply to the community. This research is based on descriptive research, which is a study that aims to describe the situation or phenomenon that occurs as clearly as possible. In this case what will be described is the rule of law, the crime of embezzlement of four-wheeled vehicles, obstacles encountered in the Pekanbaru City Police Department.The conclusion is that fraud is caused by economic factors that force a person to commit a crime. To get the defendant's money, he bought a car which the defendant pawned to get the amount of money the defendant used for his daily needs. After the elements of a criminal offense have been fulfilled, the perpetrators of these crimes must be sentenced. The embezzlement crime is regulated in article 372 of the Criminal Code which carries a maximum sentence of 4 years in prison.Keywords: Investigation – Embezzlement.